2019
DOI: 10.1111/medu.13936
|View full text |Cite
|
Sign up to set email alerts
|

Cost evaluations in health professions education: a systematic review of methods and reporting quality

Abstract: Context High‐quality research into education costs can inform better decision making. Improvements to cost research can be guided by information about the research questions, methods and reporting of studies evaluating costs in health professions education (HPE). Our objective was to appraise the overall state of the field and evaluate temporal trends in the methods and reporting quality of cost evaluations in HPE research. Methods We searched the MEDLINE, CINAHL (Cumulative Index to Nursing and Allied Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
81
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(98 citation statements)
references
References 48 publications
(71 reference statements)
4
81
0
1
Order By: Relevance
“…Nevertheless, in line with Foo et al. 's conclusions, we experienced challenges such as using the right nomenclature, choosing the correct methodology and putting a price on the value‐side of selection. The recently published Association for Medical Education in Europe guide on how to read studies on educational costs and some exemplary studies (e.g.…”
mentioning
confidence: 60%
See 4 more Smart Citations
“…Nevertheless, in line with Foo et al. 's conclusions, we experienced challenges such as using the right nomenclature, choosing the correct methodology and putting a price on the value‐side of selection. The recently published Association for Medical Education in Europe guide on how to read studies on educational costs and some exemplary studies (e.g.…”
mentioning
confidence: 60%
“…However, this information is often not available: studies on costs are extremely scarce in HPE and studies including value are even more rare. Furthermore, the systematic review by Foo and colleagues in this issue of Medical Education concluded that the quality of most of the available research is substandard and has not increased since the beginning of this century. They found that shortcomings in the cost‐evaluation literature are mostly related to the methodology and reporting specific to these analyses.…”
mentioning
confidence: 99%
See 3 more Smart Citations